PROHIBITION OF ALCOHOL IN QURAN AND BIBLE (A RESEARCH AND ANALYTICAL REVIEW) - Dr. HM Azhar Usama; Dr. Muhammad Riaz; Dr. Aziza Khan; Noorjahan Begum; Dr. Muhammad Asif; Dr. Muhammad Hamza (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Alcohol is a cause of physical, spiritual, mental and social corruption, disgrace, humiliation, torture, indecency, indecency, vulgarity and bad behavior. Drinking alcohol affects the five senses, especially the eyesight, which is almost far-sightedness, is affected and the eyes of the drunkard become red. In addition, the sense of smell (the power of smell), the power of touch (the power of touch), the power of hearing (the power of hearing) and the power of taste are affected. Alcohol affects the brain. Affects all three parts (cerebrum, cerebellum and medulla oblongata). Disrupts the digestive system and disturbs the physical balance, which causes many alcoholics to lie in the garbage and drains. Libido at its peak. Goes away, alcoholics cannot discriminate in relationships and thus mothers, sisters and daughters are the targets of gratification in homes. The bad behavior of a drunkard causes infamy and disgrace to the country, nation, religion, family and society. That is why the Lord Almighty revealed its sanctity in all religions. Here we mentioned the sanctity and prohibition of alcohol in Christianity and Islam. In this research paper, it is specifically stated that Islam has strongly prohibited the consumption of drugs and alcohol and has strictly prohibited its use. Drinking alcohol or using drugs is very harmful and fatal for a person in terms of both religion and world. The concept of a pure society presented by Islam, if it is to be implemented, then the society must be cleansed of drugs, cruelty, hatred, enmity, murder, robbery, robbery, theft, adultery, obscenity, disrespect and indecency. If it is to be done, it is necessary to protect people from alcoholism and drugs and to protect the areas.